The human aspects of project management, vol. 2: Human resource skills for the project manager - Verma, Vijay K., 1949-; Project Management Institute (Newtown Square, PA : Project Management Institute, 1996)
This book offers guidelines that can be used to develop and implement the human skills appropriate to project management: communication, motivation, negotiation, conflict resolution, conflict and stress management, and leadership.
v. 1. Organizing projects for success -- v. 2. Human resource skills for the project manager -- v. 3. Managing the project team.
Includes bibliographical references and indexes.
oif 18/09/14
Loan
Keywords: Project management; Matrix organization; Teams in the workplace